Akulturasi Hadis dengan Tradisi Perkawinan Masyarakat Batak Angkola: Studi di Kabupaten Tapanuli Selatan, Sumatera Utara - Hasan Bakti Nasution; Sulidar Sulidar; Muhammad Amin; Uqbatul Khair Rambe; Ismail Fahmi Arrauf Nasution (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Acculturation of Hadith with the Marriage Tradition of the Angkola Batak Society:Study in South Tapanuli Regency, North SumateraThis article aims to analyze the hadith of the Prophet Muhammad. which was constructed through the practice of the marriage tradition of the Angkola Batak community in South Tapanuli, North Sumatra. Methodologically, this research was conducted using an ethnomethodological method with an anthropological approach and the science of hadith related to the search matan hadith, the research style was qualitative in the form of field research. This study found that traditional inheritance in the marriage tradition of the Angkola Batak community provides a strengthening space for the implementation of hadith values that arise in the practice of leaving fortune tellers to determine the auspicious day of marriage, abandoning the prohibition of marrying a clan, not carrying out the recommendation to marry the daughter of a mother's brother, carrying out deliberations (markobar) customs, wages and advise the bride and groom. The implementation of the Angkola Batak wedding tradition includes five parts. First;: mangaririt boru, asking the bride and groom who will be betel nut, Second: manyapai boru, which is asking a girl who previously did not know if she is willing to live together. Third; manulak sere sahatan, which is delivering the dowry. Fourth; Martahi, namely deliberation for the submission of work (horja). Fifth; mangalehen manganese pamunan means a farewell meal for a daughter because she will be sent to her husband's house. Lastly; mangolat is interpreted with permission. The elements constructed in the Angkola Batak tradition are found in the customary values and behavioural systems of the marriage tradition, which are believed to be the path to a sakinah, mawaddah, wa al-rahmah family life.